2012
DOI: 10.1093/ntr/nts180
|View full text |Cite
|
Sign up to set email alerts
|

Initial Reactions to Tobacco Use and Risk of Future Regular Use

Abstract: Introduction: Studies suggest that initial smoking pleasure influences future smoking behavior. We investigated how initial reactions to cigarettes or Swedish smokeless tobacco (snus) were associated with future use among 10,708 adults from the Swedish Twin Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…This research suggests a positive association between pleasant subjective experiences during the initial experience and later adult smoking (Ursprung et al, 2011) and the number of cigarettes smoked by adult smokers (DiFranza et al, 2004). However, other studies have also found a positive association between unpleasant subjective experiences at first smoking experience and progression to regular smoking (DiFranza et al, 2004; Ríos-Bedoya et al, 2009; Klein et al, 2013; Zabor et al, 2013). Chemical additives in cigarettes (Rabinoff et al, 2007) may influence the number and degree of subjective experiences at first use, as some individuals may be more sensitive to nicotine exposure than others.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This research suggests a positive association between pleasant subjective experiences during the initial experience and later adult smoking (Ursprung et al, 2011) and the number of cigarettes smoked by adult smokers (DiFranza et al, 2004). However, other studies have also found a positive association between unpleasant subjective experiences at first smoking experience and progression to regular smoking (DiFranza et al, 2004; Ríos-Bedoya et al, 2009; Klein et al, 2013; Zabor et al, 2013). Chemical additives in cigarettes (Rabinoff et al, 2007) may influence the number and degree of subjective experiences at first use, as some individuals may be more sensitive to nicotine exposure than others.…”
Section: Introductionmentioning
confidence: 86%
“…Studies of subjective experiences during initial cigarette use have identified “positive” (i.e., euphoria, relaxation), “negative” (i.e., nausea, coughing) (Zabor et al, 2013), and “neutral” subjective experiences (i.e., “dizziness”) (Ríos-Bedoya et al, 2009). This research suggests a positive association between pleasant subjective experiences during the initial experience and later adult smoking (Ursprung et al, 2011) and the number of cigarettes smoked by adult smokers (DiFranza et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, early negative subjective drug effects should exert a protective effect against continued drug use, but the literature has not found consistent evidence to support this. Negative initial reactions to tobacco and cannabis have been found to increase odds of later cannabis abuse/dependence (Agrawal, et al, 2014), but other studies found no effect on odds of becoming a regular smoker (Baggio, et al, 2014; Zabor, et al, 2013) or future or lifetime use of cannabis (Davidson & Schenk, 1994). Studies have also found that negative alcohol outcome expectancies increase as alcohol consumption increases (Gadon, Bruce, McConnochie, & Jones, 2004) and may be important for alcohol treatment outcomes (Jones & McMahon, 1994, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Following from positive reinforcement models of substance use risk (MacKillop & de Wit, 2013), individuals who have more positive (e.g., relaxation, pleasant) early experiences with alcohol, cigarettes, and cannabis are more likely to continue use of the substance and later develop addiction (Agrawal, Madden, Bucholz, Heath, & Lynskey, 2014; Baggio, et al, 2014; Buchmann, et al, 2013; Zabor, et al, 2013). Theoretically, early negative subjective drug effects should exert a protective effect against continued drug use, but the literature has not found consistent evidence to support this.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals differ in how sensitive they are to the effects of nicotine (Pomerleau, Collins, Shiffman, & Pomerleau, 1993). For example, individuals that experience positive sensations upon trying their very first cigarette continue to use regularly (Hirschman, Leventhal, & Glynn, 1984; Zabor et al, 2012) due primarily to the pharmacological effects of nicotine (Subramaniyan & Dani, 2015). Individuals that experience pleasant sensations when smoking their first cigarette develop symptoms of nicotine dependence at a faster rate than those for whom that first cigarette was not pleasant (DiFranza et al, 2004; Pomerleau, Pomerleau, & Namenek, 1998).…”
mentioning
confidence: 99%